PANDHU MUKSA DALAM PAMUKSA KARYA KI NARTO SABDO - Triyogo, YB Rahno (Institut Seni Indoensia Surakarta, 2017)
Pamuksa was a play told us that heaven and hell were a mere options. Heaven was togetherness withthe God, the divine source of happiness, while hell was the opposite. Pandhu and Tremboko hadpicked the fruit of their choices. Pandhu went to hell not because of his fault and sin but rather by hisown choice. Pandhu’s choice to prefer worldly life was a reckless attitude that did not reflect sarirahangrasa wani. Due to the devotions of his sons: Bratasena and Arjuna, and with support by theangels, Pandhu was saved. This study discussed the moral aspect, therefore a moral approach wasused. The result of this study were the moral messages that first, if humans wanted to be happy thenthe heavenly value was the first and foremost priority. Second, that children’s devotions to the parentswas able to save the parents from disgrace which in Javanese tradition was referred as mikul dhuwur,mendhem jero.Keywords: heaven and hell, option, children’s devotion, save.